(untitled) (International relations and international law Journal, 2019)
In international law, an important aspect remains the question of the legal personality of an individual, which they began to examine in more detail from the middle of the XX th century. This was due to the fact that by this time the general concepts of human rights had been worked out. The adopted international documents on human rights made it possible to closely approach the solution of another equally important issue of the legal personality of an individual. Despite the fact that the topic in the field of international law seems to be investigated, regarding both the status and the legal status of a person in international law, we set a goal in clarifying how it is currently studying this problem. Therefore, this article was aimed primarily at finding out what constitutes the basis of the non-recognition or partial non-recognition of the legal personality of an individual. First of all, the article focused on the diversity of opinions of scientists, and, on this basis, tried to uncover the essence and semantic meaning of each of them, as well as identify some key elements,contributing to the non-recognition of the legal personality of an individual. Key words: individual, natural person, subject of international law, legal personality.